Western Mesoamerican calendars and writing systems : proceedings of the Copenhagen Roundtable - Clemmensen, Mikkel Bøg, (Archaeopress pre-Columbian archaeology ;, 2023)
Mesoamerica is one of the few places to witness the independent invention of writing. Bringing together new research, papers discuss the writing systems of Teotihuacan, Mixteca Baja, the Epiclassic period and Aztec writing of the Postclassic. These writing systems represent more than a millennium of written records and literacy in Mesoamerica.